The Effect of Group Counseling with Thought Stopping Techniques in reducing Students' Social Media FoMO at SMAN 2 Gunung Talang - Yusmizar, Abdi Thoyib; Irman, Irman; Masril, Masril; Darimis, Darimis; Al-Momani, Ammar (International Journal of Research in Counseling, 2025)
The main problem in this research is that there are students who have high social media FoMO behavior. The main problem is the high level of FoMO behavior on social media, one technique that can be used to reduce it is through thought stopping technique group counseling. The aim of this research is to determine the effect of group counseling using thought stopping techniques in reducing social media FoMO in students. The sample in this study consisted of 11 students for the experimental group based on the characteristics of students who have social media FoMO behavior. The data analysis technique used is the statistical t-test. The design used is a pre-experimental design with a one group pre-test – post-test design type because at the implementation stage of this design a pre-test is given first before new actions are given followed by a post-test. The results of this research show that group counseling using the thought stopping technique in reducing social media FoMO in students has a significant effect with the results obtained with a value of (thit = 10.5) > "t" (ttable 2.22) at a significant level of 5%